A Systematic Study: The Use of Artificial Intelligence and Search Engines in Mathematics Learning - Yuanda Oktrin Lay; Jailani (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
Mathematics education in the digital age faces new challenges and opportunities with the advent of technology. Artificial Intelligence and Search Engines have become tools that are often used in the process of searching for information and learning. This study aims to identify, map, and synthesize the latest scientific research on the role, impact, and challenges of using artificial intelligence and search engines in the context of mathematics education. The method used is a systematic study of 26 relevant articles from 2016 to 2025, which are included in the Q1, Q2, and Q3 indices, obtained through a selection process similar to the PRISMA guidelines. The results of the thematic analysis revealed several key findings: (1) There was a significant boom in research trends in 2024-2025, dominated by Generative AI research (such as ChatGPT). (2) The role of artificial intelligence has evolved from intelligent tutor systems (ITS) to dialogic personal tutors (chatbots) and adaptive learning platforms. (3) The role of traditional search engines as information retrieval tools is shifting and, in some cases, being replaced by generative AI capable of synthesizing answers. (4) Consistent positive impacts reported include increased motivation, problem solving, and self-efficacy, but these are offset by challenges related to accuracy, bias, and the urgent need for AI literacy among teachers and students. This study concludes that the state of mathematics learning technology is rapidly shifting toward AI-based systems, which requires pedagogical adaptation and further research on their integration in the classroom.